(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objectives: To determine the frequency of thyroid dysfunction in first trimester of pregnancy. Study design: Descriptive, cross sectional. Study duration: February 2023 to July 2023. Materials & Methods: Total 305 women having pregnancy of gestational age 8-16 weeks of 18-40 years of age were selected. Patients with known diabetes mellitus and hypertension, CRF & medication that can affect thyroid functions were excluded. Thyroid function tests were performed on a venous blood sample, and the presence or absence of thyroid dysfunction was noted. Results: Participants in the study were between the ages of 18 and 40, with an average age of 27.89 ± 4.53 years. Of the 104 patients, 65.82 percent were between the ages of 20 and 30. At birth, they were 7.79 ± 1.64 weeks old. The average BMI was found to be 27.54 ± 3.00 kg/m2. Thyroid impairment was found in 47 (15.19%) of the pregnant women in our study. Conclusion: This study concludes that the frequency of thyroid dysfunction in pregnant females is quite high.